2014
DOI: 10.1111/ped.12318
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of telediagnosis of fetal heart disease using ultrasound images transmitted via the Internet

Abstract: We verified the feasibility of telediagnosis of fetal disease by (i) grading telediagnosis by a pediatric cardiologist into five confidence levels; and (ii) comparison of fetal telediagnosis with hands-on fetal diagnosis or postnatal diagnosis. In 114 patients suspected of having heart disease (real time, n = 15; recorded image transmission, n = 99), 79 patients were in level 5 (excellent), 17 in level 4 (good), eight in level 3 (fair), 10 in level 2 (poor), and no patients in level 1 (bad). The average was 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Some limitations must be considered. The accuracy of the service as well as its cost‐effectiveness should be evaluated (Fabbrocini et al., ; Hishitani et al., ; Torres‐Pereira et al., ). In a previous study, Torres‐Pereira et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some limitations must be considered. The accuracy of the service as well as its cost‐effectiveness should be evaluated (Fabbrocini et al., ; Hishitani et al., ; Torres‐Pereira et al., ). In a previous study, Torres‐Pereira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations must be considered. The accuracy of the service as well as its cost-effectiveness should be evaluated (Fabbrocini et al, 2008;Hishitani et al, 2014;Torres-Pereira et al, 2008). In a previous study, Torres-Pereira et al (2013) demonstrated that in 88% of cases, one of two remote consultants was capable of providing the right diagnosis when compared with the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true in rural locations where it is more convenient and cost-effective to provide telemedicine services than transport patients to higher echelons of care. [5][6][7][8][9] We recently compared the sensitivity and accuracy of 2368 teleultrasounds with the results of published literature for on-site ultrasounds and observed that they were similar. This is true for several reasons.…”
Section: Introductionmentioning
confidence: 94%
“…There are scarce data regarding the sensitivity and accuracy of teleultrasound . There is no standard detection rate for the reference study (on‐site ultrasound) and often no robust method of validation (ie, postnatal diagnosis).…”
mentioning
confidence: 99%
“…6,7 There are scarce data regarding the sensitivity and accuracy of teleultrasound. 8,9 There is no standard detection rate for the reference study (on-site ultrasound) and often no robust method of validation (ie, postnatal diagnosis). A large systematic review of 36 studies noted overall sensitivity of 40.4%, with a range of 13.3% to 82.4% 10 for identifying structural anomalies.…”
mentioning
confidence: 99%